2018
DOI: 10.1111/trf.15087
|View full text |Cite
|
Sign up to set email alerts
|

Susceptible and protective HLA‐DR and HLA‐DQ alleles for Fya alloimmunization in the Croatian population

Abstract: BACKGROUND Alloimmunization is a known risk of transfusion therapy caused by exposure to foreign RBC antigens. However, alloimmunization is not observed in all transfused patients. Human leukocyte antigen (HLA) molecules may contribute to the recognition and presentation of foreign antigens and to the potency of immune responses that result in the production of antibodies. The aim of this study was to determine the association of HLA‐DR and HLA‐DQ polymorphisms with alloimunization to Fya antigen in Croatian p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…A strong correlation between anti-Fy a alloimmunization and HLA-DRB1*04 and HLA-DRB1*15 genes, as well as with HLA-DRB1*04~DQB1*03 and HLA-DRB1*15~DQB1*06 haplotypes, was also observed [71,72]. In addition, the protective role of the HLA-DQB1*02 gene and DRB1*03~DQB1*02 and DRB1*07~DQB1*02 haplotypes for Fy a alloimmunization was also detected [72]. All presented data support the theory that the immunogenicity of a given RBC antigen is related both to the nature of the antigen and the capability of specific HLA class II molecules to present the derived peptides to T lymphocytes and initiate the immune response [23].…”
Section: Disease Association Studiesmentioning
confidence: 76%
See 1 more Smart Citation
“…A strong correlation between anti-Fy a alloimmunization and HLA-DRB1*04 and HLA-DRB1*15 genes, as well as with HLA-DRB1*04~DQB1*03 and HLA-DRB1*15~DQB1*06 haplotypes, was also observed [71,72]. In addition, the protective role of the HLA-DQB1*02 gene and DRB1*03~DQB1*02 and DRB1*07~DQB1*02 haplotypes for Fy a alloimmunization was also detected [72]. All presented data support the theory that the immunogenicity of a given RBC antigen is related both to the nature of the antigen and the capability of specific HLA class II molecules to present the derived peptides to T lymphocytes and initiate the immune response [23].…”
Section: Disease Association Studiesmentioning
confidence: 76%
“…A study from the Czech population observed an association of HLA‐DRB1*15 and DQB1*06 genes with RBC antibody multiresponder status, but also an association of three frequent antibody combinations (anti‐C+D, anti‐E+c and anti‐E+Cw) and HLA‐DRB1 genes (HLA‐DRB1*15, HLA‐DRB1*13 and HLA‐DRB1*03, respectively) . A strong correlation between anti‐Fy a alloimmunization and HLA‐DRB1*04 and HLA‐DRB1*15 genes, as well as with HLA‐DRB1*04~DQB1*03 and HLA‐DRB1*15~DQB1*06 haplotypes, was also observed . In addition, the protective role of the HLA‐DQB1*02 gene and DRB1*03~DQB1*02 and DRB1*07~DQB1*02 haplotypes for Fy a alloimmunization was also detected .…”
Section: Disease Association Studiesmentioning
confidence: 99%
“…In this study, we investigated the distribution of HLA-Class II variants within subgroups of multi-responders to RBC alloantigens, with the aim of elucidating associations between HLA-Class II alleles, Rh phenotypes, and RBC alloimmunization. In the previous studies, HLA-DRB1*15 has been associated with multiple RBC antibody responsiveness (13)(14)(15) and with anti-Fy a alloimmunization (10,11,16). Here we found that the DRB1*15 variant was twice as frequent in multi-responders with the D-negative phenotype as in RhD-positive multi-responders.…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, Baleotti et al [21] had concluded that there was an overrepresentation of HLA-DRB1*07 in patients alloimmunized with anti-Di a compared to non-alloimmunized patients, 75% and 27%, respectively. both) [19,37].…”
Section: Interpretationsmentioning
confidence: 99%
“…A relationship between HLA polymorphisms and immune responses to various RBC antigens has been established, and these include Duffy a [ 18 , 19 ], Kell [ 20 ], Diego [ 21 ] and Kidd a [ 22 ]. Noizait‐Pirenne et al conducted a study to identify the HLA‐DRB1 restriction molecules within the anti‐Fy a and anti‐K groups in Caucasians.…”
Section: Introductionmentioning
confidence: 99%